2008
DOI: 10.2464/jilm.58.104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of SiC particle–AZ31B magnesium alloy machined chips composites prepared by hot extrusion after ECAP

Abstract: Wear resistance and mechanical properties of hot extruded AZ31B/SiC particle composite, where the hot extrusion billets were processed by ECAP, were investigated. Uniform dispersion of SiC particles was observed after extrusion for the mean particle size of 1.2ϳ11 mm constituting 0 to 6% volume fraction of SiC particle content, where the particles had been thinly adhered to the surface of the machined chips of ECAP-hot extrusion samples before extrusion. However, when the SiC particle size is under 3 mm, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although the studies mentioned above have targeted single-phase materials, the solid-state recycling of machined chips into composite materials has also been attempted. These have included magnesium-based composites with SiC particles (Aida et al, 2008) and aluminium-based composites with reinforcing particles such as tungsten, which was adopted by Gronostajski et al (1996), and SiC, which was utilised by Tekkaya et al (2009). It was recently revealed that the hot extrusion of aluminium alloy machined chips with pure aluminium powder added as a binder achieves better bonding and results in improved mechanical properties for recycled products made from two-phase materials (Sherafat et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Although the studies mentioned above have targeted single-phase materials, the solid-state recycling of machined chips into composite materials has also been attempted. These have included magnesium-based composites with SiC particles (Aida et al, 2008) and aluminium-based composites with reinforcing particles such as tungsten, which was adopted by Gronostajski et al (1996), and SiC, which was utilised by Tekkaya et al (2009). It was recently revealed that the hot extrusion of aluminium alloy machined chips with pure aluminium powder added as a binder achieves better bonding and results in improved mechanical properties for recycled products made from two-phase materials (Sherafat et al, 2009).…”
Section: Introductionmentioning
confidence: 98%